METODE PEMBELAJARAN TAHFIDZ AL-QUR’AN SANTRI USIA SEKOLAH DASAR DI RUMAH TAHFIDZ BAYTUL HUFFADZ JATIUWUNG KOTA TANGERANG - Guci, Alexander; Sukmana, Jaya (STAI Asy-Syukriyyah, 2023)
Seeing the reality of Indonesian society, there are very many people who are educated but they are not yet close to noble character. This is a serious step for the nation to fix deficiencies in education, one of which is through learning and memorizing the holy verses of the Koran from an early age. This is expected to be able to improve the quality of education and create a generation of people with noble character. This is also so that children are happy with the Qur'an as a guide for human life, if the way it is conveyed is also fun, of course this requires a learning method for tahfidz al-Qur'an to support success. The approach used in this study is a qualitative approach by taking the background of the Tahfidz Baytul Huffadz House. The research was conducted starting in February 2017 in Ledug Village 02/06 Kel. Keroncong Kec. Jatiuwung Tangerang City. The informants were 3 students, 1 Al-Qur'an teaching staff, and 1 head of the Tahfidz House. Data collection techniques using observation, documentation and interviews. Then the data is transcribed into complete data. Data transcripts were analyzed using deductive, inductive methods.The results of the study show that the method applied in learning the tahfidz of the Qur'an is very useful for improving the performance of the Baytul Huffadz Tahfidz House and its role as an educational institution in improving the quality of education and creating a generation of noble people.